Analisis Kinerja Lightning Arrester (LA) pada Pemancar Radio Di Gedung RRI Medan - Akbar Wirayuda; Zuraidah Tharo; Parlin Siagian (CV. Hawari, 2025)
This study aims to evaluate how well lightning arresters protect the radio transmitter system in the RRI Medan Building from voltage surge disturbances caused by lightning strikes. Measurement of grounding resistance, field observation, and interviews with relevant technicians are all procedures used. The results of the study indicate that a grounding system with a resistance of less than 5 ohms can reduce voltage surges to a protection level of 99%. Choosing the distance of the arrester installation and conducting periodic maintenance are two important components in maintaining a reliable lightning protection system. It is expected to improve the safety of the device and the continuity of radio broadcasting services in extreme weather situations.